Comparison of treprostinil and oral sildenafil for the treatment of persistent pulmonary hypertension of the newborn: a retrospective cohort study - Wei, Enhuan; Chen, Xiu-hua; Zhou, Si-Jia (Frontiers in Pediatrics, 2023)
Background: This study aims to evaluate the effectiveness of treprostinil and oral sildenafil in managing persistent pulmonary hypertension of newborns (PPHN).We conducted a retrospective cohort study of 42 neonates with PPHN treated with continuous intravenous treprostinil or oral sildenafil from January 2020 to October 2022 in China. Outcomes assessed included echocardiographic pulmonary artery systolic pressure (PASP), shunt direction, and arterial blood gas measures.Results: Treprostinil lowered PASP and improved oxygenation significantly better than sildenafil on days 1, 2 and 3 of treatment (P<0.05). Treprostinil also corrected shunt direction faster than sildenafil (P<0.05). The duration of mechanical ventilation, length of NICU stay, and overall hospital stay did not significantly differ between the two groups (P>0.05).Treprostinil effectively lowers pulmonary artery pressure and improves oxygenation in neonates with PPHN, without being associated with severe complications. It may serve as a beneficial adjunct therapy for neonates with PPHN.